Prevalence of nomophobia and its ill effects among undergraduate medical students - Bansode, Saroja G.; Acharya, Namrata A.; Nagaonkar, Ajit S. (International Journal Of Community Medicine And Public Health, 2025)
Background: Mobile phones, once designed solely for communication, have evolved into multifunctional devices that play a significant role in daily life. However, excessive usage has been linked to various physical and psychological issues, including nomophobia. Nomophobia is increasingly prevalent, particularly among young adults, including medical students who are frequent users of mobile phones for both academic and non-academic purposes. This study aims to explore the prevalence of nomophobia and its associated health effects among undergraduate medical students. Methods: A descriptive cross-sectional study was conducted at government medical college, Latur, from December 2019 to February 2020. A total of 200 undergraduate MBBS students were included using purposive sampling. A pre-tested, self-administered questionnaire was used to assess socio-demographic factors, mobile phone usage, and health effects. Nomophobia was measured using test of mobile phone dependence (TMD) brief, and data was analyzed using descriptive and inferential statistics. Results: The study found that 82% of students were classified as nomophobic. Nomophobia was significantly associated with the year of study, age, and frequency of mobile phone checking. The most common health issues reported were sleep disturbances (46%), eye strain (43%), and headaches (43%). Additionally, 20% reported poor academic performance, and 18% experienced anxiety. The primary purpose of mobile phone use was calling and texting, followed by music, with usage being most common when students were alone (66%). Conclusions: The study highlights the high prevalence of nomophobia among medical students and its negative impact on physical and psychological health. Awareness about the potential health risks associated with excessive mobile phone use is crucial for promoting healthier usage habits.